A labour rights-based critique of Nozick’s entitlement theory - Söderlund, Sasha (The Stellenbosch Socratic Journal, 2024)
Robert Nozick’s libertarian theory of justice as entitlement proposes that any transfer of private property, including one’s skills, based on voluntary consent is legitimate. Applied to the labour context, Nozick contends that labour agreements free from direct coercion are just and should be unregulated to preserve autonomy and liberty, regardless of potential exploitation. This paper argues that Nozick’s understanding of consent neglects the lived realities and socioeconomic inequalities that are evident in, for example, employment in the mica mining industry in India, and thus fails to address the unjust exploitation of workers. Mica mining is characterised by hazardous working conditions, child exploitation, and poor compensation rooted in socioeconomic desperation. This paper aims to highlight the necessity-driven, rather than consensual, participation of vulnerable members of society. Through a detailed analysis of Nozick’s libertarian principles and their application to labour in a case study of mica mining, this paper demonstrates that the overemphasis on consent and minimal state intervention integral to this theory fails to protect those most vulnerable. This critique uncovers the limitations of Nozick’s theory in addressing socioeconomic injustices and emphasises the need for a more comprehensive approach that considers social context and workers’ rights. The conclusion of this paper is that Nozick’s entitlement theory is incapable of achieving substantive justice in the context of labour rights.